Access to education and disability insurance claims - Vivika Halapuu (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2021)
The paper provides the first causal evidence of how access to education affects disability insurance (DI) claims among low-skilled youths. The research design exploits recent changes in high school eligibility criteria among a set of low-performing compulsory school graduates in Sweden. The results show that the immediate inflow into the DI system increased by 5.1 percentage points among the students who were excluded from standard high school programs. The fact that outflow from DI is very low (half of all young claimants remain in the system after 10 years) together with auxiliary findings indicating that the impact remains high during the short follow-up period suggest that the effect is likely to persist over many years. The results highlight that the design of education systems is a crucial determinant of DI claims among young people and that reforms which limit low-skilled youths' access to education can have lasting detrimental effects on their labor supply
Keywords: I24; I26; I28; 330; Access to education; Disability insurance; Education Policy